A social license to operate: pre-mining effects and activities perspective - Adeyinka Oluwayomi Omotehinse; Giorgio de Tomi (REM: International Engineering Journal)
Abstract This research proposes a new approach to recommend a responsible mining guideline on how to secure a social license to operate in Ondo state, Nigeria for oil sands mineral resources taking into account the bituminous natural effects. This is the case of bituminous oil sands in Southern Nigeria, where warm weather can induce the emission of natural bitumen fumes. Because this emission may bring occupational exposure to the local communities, mining is perceived to be an opportunity for both social-economic improvement but also an efficient approach to reduce exposure to bitumen fumes. The study investigates the importance of the perception of the society about responsible mining practices in establishing a social license for a mining operation. The results of the investigation include an appraisal of the social status, living conditions of the communities, effects of pre-mining activities and the natural impacts of bitumen from oil sand on the community. The conclusions are that the bituminous natural effects on the communities can facilitate the approval of SLO, if the company can fulfil its promises, as mining is perceived to be a welcome solution to the problems posed. In addition, the mining company must also be transparent with the community as this changes the perception of society about responsible mining practices and help in establishing SLO.